Optimal synthesis of reconfigurable planar arrays for monopulse radar applications: Use of subarrays and distributions with common aperture tail - Zhengdong Qi; Xinggan Zhang; Yechao Bai; Qiong Wang; Chunhua Yu; Hao Chen; Yangyi Lu; Shaopeng Wu (IET Microwaves, Antennas & Propagation, 2021)
Abstract An approach for the synthesis of sum and difference patterns in monopulse antennas is described. The proposed approach provides a significant reduction in the complexity of the beam‐forming network that is fulfilled by reducing the number of array elements and keeping the elements at the edges of the array that share common excitations for both sum and difference modes. An iterative constrained optimisation method is used where the non‐convex lower‐bound constraints on the beam pattern are cast as an equivalent multi‐convex optimisation problem while concurrently minimising a reweighted l1‐norm of the magnitudes of the elements in the beam‐forming weight vector. Thus, better radiation performance of beam pattern (e.g. narrower beamwidth, lower peak sidelobe level), a much narrower spatial aperture and a smaller number of elements can be achieved compared with the case of uniformly spaced arrays. To compensate for array imperfection in practice, robust beam pattern constraints are derived in the optimisation stage using a worst‐case performance optimisation technique. Numerical examples show the effectiveness and advantages of the proposed synthesis approach.